Alternative type I and I` turn conformations in the β8/β9 β-hairpin of human acidic fibroblast growth factor - Kim, Jaewon (Cold Spring Harbor Laboratory Press, 2002)
Human acidic fibroblast growth factor (FGF-1) has a β-trefoil structure, one of the fundamental protein superfolds. The X-ray crystal structures of wild-type and various mutant forms of FGF-1 have been solved in five different space groups: C2, C222(1), P2(1) (four molecules/asu), P2(1) (three molecules/asu), and P2(1)2(1)2(1). These structures reveal two characteristically different conformations for the β8/β9 β-hairpin comprising residue positions 90–94. This region in the wild-type FGF-1 structure (P2(1), four molecules/asu), a his-tagged His93→Gly mutant (P2(1), three molecules/asu) and a his-tagged Asn106→Gly mutant (P2(1)2(1)2(1)) adopts a 3:5 β-hairpin known as a type I (1–4) G1 β-bulge (containing a type I turn). However, a his-tagged form of wild-type FGF-1 (C222(1)) and a his-tagged Leu44→Phe mutant (C2) adopt a 3:3 β-hairpin (containing a type I` turn) for this same region. A feature that distinguishes these two types of β-hairpin structures is the number and location of side chain positions with eclipsed C(β) and main-chain carbonyl oxygen groups (Ψ ≅ +60°). The effects of glycine mutations upon stability, at positions within the hairpin, have been used to identify the most likely structure in solution. Type I` turns in the structural data bank are quite rare, and a survey of these turns reveals that a large percentage exhibit crystal contacts within 3.0 Å. This suggests that many of the type I` turns in X-ray structures may be adopted due to crystal packing effects.